Gabapentin reduces alcohol consumption and craving: a randomized, double-blind, placebo-controlled trial - Furieri, Fernando A; Nakamura-Palacios, Ester M (The journal of clinical psychiatry, 2007)
This study examined the efficacy of a 28-day gabapentin treatment in reducing alcohol consumption and craving. A randomized, double-blind, placebo-controlled trial was performed in a Brazilian public outpatient drug treatment center, with 60 male alcohol-dependent subjects with a mean age of 44 years and an average of 27 years of alcohol use, who consumed 17 drinks per day (165-170 g/day) over the past 90 days before baseline and had no other significant medical or psychiatric condition. Subjects were recruited between July 8, 2004, and February 24, 2005. Following screening, 60 subjects were selected and received diazepam and vitamins as treatment for acute withdrawal for at least 7 days. After the detoxification treatment, 30 subjects were randomly assigned to receive gabapentin (300 mg twice daily) for 4 weeks, and 30 subjects, with similar baseline characteristics, were randomly assigned to receive matching placebo tablets for the same period. After 28 days of treatment, the gabapentin group showed a significant reduction in both number of drinks per day and mean percentage of heavy drinking days (p = .02 for both), and an increase in the percentage of days of abstinence (p = .008), compared to the placebo group. Additionally, some improvement in obsessive-compulsive symptoms was noted in both groups after the treatment, but it resulted in a more pronounced decrease in automaticity of drinking and aspects of craving in the gabapentin group than in the placebo group. Gabapentin reduces alcohol consumption and craving, which may help patients to maintain abstinence. These results, together with the virtual absence of side effects and a favorable safety profile, support gabapentin as a potential drug for the treatment of alcohol withdrawal and dependence.